Tubulin-VDAC Interaction: Molecular Basis for Mitochondrial Dysfunction in Chemotherapy-Induced Peripheral Neuropathy - Rovini, Amandine (Frontiers in Physiology, 2019)
Tubulin is a well-established target of microtubule-targeting agents (MTAs), a widely used class of chemotherapeutic drugs. Yet, aside from their powerful anti-cancer efficiency, MTAs induce a dose-limiting and debilitating peripheral neurotoxicity. Despite intensive efforts in the development of neuroprotective agents, there are currently no approved therapies to effectively manage chemotherapy-induced peripheral neuropathy (CIPN). Over the last decade, attempts to unravel the pathomechanisms underlying the development of CIPN led to the observation that mitochondrial dysfunctions stand as a common feature associated with axonal degeneration. Concomitantly, mitochondria emerged as crucial players in the anti-cancer efficiency of MTAs. The findings that free dimeric tubulin could be associated with mitochondrial membranes and interact directly with the voltage-dependent anion channels (VDACs) located in the mitochondrial outer membrane strongly suggested the existence of an interplay between both subcellular compartments. The biological relevance of the interaction between tubulin and VDAC came from subsequent in vitro studies, which found dimeric tubulin to be a potent modulator of VDAC and ultimately of mitochondrial membrane permeability to respiratory substrates. Therefore, one of the hypothetic mechanisms of CIPN implies that MTAs, by binding directly to the tubulin associated with VDAC, interferes with mitochondrial function in the peripheral nervous system. We review here the foundations of this hypothesis and discuss them in light of the current knowledge. A focus is set on the molecular mechanisms behind MTAs interference with dimeric tubulin and VDAC interaction, the potential relevance of tubulin isotypes and availability as a free dimer in the specific context of MTA-induced CIPN. We further highlight the emerging interest for VDAC and its interacting partners as a promising therapeutic target in neurodegeneration.